A study of intrauterine fetal death in a tertiary care hospital - Saha, Divya; Kurude, Vilas N.; Mundhe, Sharvari (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Intrauterine fetal death is a major obstetrical complication and a devastating experience for parents as well as obstetricians. If the causes of IUFD can be found, an effective strategy for prevention of IUFD can be formed and maternal complications can thus be prevented. This study aims at identifying the various causes, etiological factors and complications of IUFD. Methods: Prospective observational study was carried out in a tertiary care hospital from 1st January 2016 to 31st July 2017. Results: Total number of deliveries during the study period was 3944 and still birth was 170. Still birth percentage was 4.31.Majority of patient belonged to maternal age group of 21-30 year of age that is 138 out of 170 around 68.5%. Only 8.82% of patients presenting with IUFD were having more than three antenatal visits. Among 61 cases (35.8%) cause was not identified while 109 cases cause was identified. Hypertensive disorder contributed to major cause of IUFD i.e. 34 out of 170 (20%) Maternal complications like hypovolemic shock occurred in 13 out of 170 (7.6%), Acute Renal failure 7 out of 170 (4.11), Sheehan syndrome. Maternal mortality was 3 out of 170 cases. Conclusions: Despite availability of modern interventions like ultrasonography, Non stress test, majority of the causes of IUFD remains unknown. Early diagnosis and delivery is important in cases of IUFD to prevent various complications like septicaemia, acute renal failure, DIC, hypovolemic shock etc.